STUDY OF RUSTIC ARCHITECTURE CONCEPT IN MERCATO RESTAURANT, SHANGHAI - Farrel Ghifari; Ari Widyati Purwantiasning (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Indonesia is one of the countries that has a tropical climate with 2 seasons namely dry season and rainy season, the rainy season in Indonesia has a large average rainfall rate of 50mm / baseline and an average temperature of 20 °C. Indonesia Has a large diversity of flaura and fauna, one of which is teak wood which is the best wood produced from Indonesia that has high quality, straight-stemmed and can grow up to a height of 30-40 meters on the Java islands. Rustic architecture is a concept that focuses on the natural impression so as to produce a warm atmosphere on the application of the concept. Rustic architecture concept has basic principles as a reference application of rustic architecture concept in designing restaurant buildings, namely the use of dominant wood materials, unfinished on the wall, the use of materials derived from nature, the use of natural colors on the part of the shaper of the room, namely walls, floors and ceilings, the last is to use materials that impress old. This research uses qualitative descriptive method to know about the application of rustic architecture in restaurant buildings, the analysis is done in a qualitative descriptive way with a reference to the principles of rustic architecture. The purpose of this research aims to know the application of rustic architectural principles to restaurant buildings. The conclusion obtained is that rustic architecture can be applied to the restaurant using rustic architectural principles so as to make the atmosphere of the restaurant warm and natural in its application Keyword: Rustic Architecture, Natural, Restaurant